The Welfare Cost of Homicides in Brazil: Accounting for Heterogeneity in the Willingness to Pay for Mortality Reductions - Daniel R. C. Cerqueira; Rodrigo R. Soares (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2012)
This paper estimates the health dimension of the welfare cost of homicides in Brazil incorporating age, gender, educational, and regional heterogeneities. We use the marginal willingness to pay approach from the “value of life” literature to assign monetary values to the welfare cost of increased mortality due to violence. The results indicate that the present discounted value of the welfare cost of homicides in Brazil corresponds to roughly 78% of the GDP or, measured in terms of yearly flow, 2.3%. The analysis also indicates that reliance on aggregate data to perform such calculations, without taking into account the relevant dimensions of heterogeneity, can lead to biases of the order of 20% in the estimated social cost of violence
Keywords: I18; J18; K42; O57; 330; Wert des Menschenlebens; Gewalt; Wohlfahrtsanalyse; Zahlungsbereitschaftsanalyse; Brasilien